Anti-Müllerian Hormone in the Diagnosis and Prediction of Premature Ovarian Insufficiency - Anderson, Richard A.; Nelson, Scott M. (Seminars in Reproductive Medicine, 2020)
The menopause and its pathological version, premature ovarian insufficiency (POI), are characterized by the cessation of follicle growth in the ovary, with consequent lack of estrogen production and amenorrhea. The measurement of a specific product of ovarian follicles would therefore be expected to be a valuable biomarker in women with POI, and to be of likely clinical value in the diagnosis and perhaps prediction of POI. Anti-Müllerian hormone (AMH) is produced by the granulosa cells of growing follicles and is therefore likely to be of value in this context. Current data indicate that measurement of AMH is an accurate indicator of POI in many situations and has diagnostic validity and may facilitate more timely diagnosis. AMH seems to be of limited value in predicting age at natural menopause, even with multiple measurements, and there are scarce data regarding prediction of POI, other than when it is imminent, and in some contexts where there is an immediate iatrogenic threat to ovarian function. AMH therefore appears to have considerable value as a diagnostic test for POI, but apart from highlighting broadly those at increased risk, it has inadequate precision to be able to predict accurately the timing of onset of impending POI.
Keywords: AMH; ovarian reserve; POI; menopause; biomarker